1994
DOI: 10.1177/104063879400600410
|View full text |Cite
|
Sign up to set email alerts
|

Canine Mast Cell Tumors: A Comparison of Staining Techniques

Abstract: Abstract. Twelve histochemical methods; affinity staining with avidin peroxidase, wheat germ agglutinin, and concavalin-A agglutinin; and an immunohistochemical stain with Kpl (CD68) antibody were compared for their relative effectiveness in staining canine mast cell tumors. Stains were compared in 28 mast cell tumors and 19 histiocytomas. The effectiveness of the histochemical methods and the lectins decreased as the mast cells became less differentiated. None of the staining methods were positive on histiocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…22 It has been assumed that this decrease in the staining pattern is due to the lack of production or storage of cellular components that react with the stain. 22 We hypothesized that well-differentiated MCTs have a stronger cytoplasmic expression of tryptase than poorly differentiated MCTs and that such a difference in expression could be used to predict the biologic behavior of canine cutaneous MCTs. To test these hypotheses a retroprospective study was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…22 It has been assumed that this decrease in the staining pattern is due to the lack of production or storage of cellular components that react with the stain. 22 We hypothesized that well-differentiated MCTs have a stronger cytoplasmic expression of tryptase than poorly differentiated MCTs and that such a difference in expression could be used to predict the biologic behavior of canine cutaneous MCTs. To test these hypotheses a retroprospective study was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…However, Gray et al, reported that 400 mg/kg carbendazim did not cause any histopathological damage the liver of rats dosed from weaning until 105 days of age (Gray et al,1990). In contrast male mice fed 5000 mg/kg carbendazim in diet showed centrilobular hypertrophy, necrosis and swelling of liver cells (Simoes and Schoning, 1994). Igbedioh and Akinyele have observed necrotized cells and oedema in the liver of rats given benomyl (WHO/IPCS, 1993).…”
Section: Figmentioning
confidence: 99%
“…It is expressed with a more intense staining in macrophages than in monocytes but also stains granulocytes and mast cells. 22 The purpose of the current study was to characterize the histological features of the multiple atypical mucosal xanthomas observed in the oral cavity and upper gastrointestinal tract of a dog and to compare these features with those of human verruciform xanthomas.…”
mentioning
confidence: 99%